Confinement of fluorine anions in nickel-based catalysts for greatly enhancing oxygen evolution activity. Issue 30 (13th March 2020) - Tong, Yun; Mao, Hainiao; Chen, Pengzuo; Sun, Qiong; Yan, Fei; Xi, Fengna
Abstract : A simple fluorine treatment was developed to confine abundant fluorine anions into Ni-based catalysts to greatly enhance OER catalytic activity. Abstract : Herein, we highlighted fluorine-anion-modification as a useful method for enhancing OER catalytic activity. Fluorine-anion-doped Ni foam exhibits an almost 10-fold enhancement in OER catalytic activity. Moreover, fluorine-anion-modification could be used as a general method to greatly increase the OER activity of NiAl LDHs. The strongly electronegative F anion is favorable to build weak metal–fluorine bonds, which easily break to form active species of nickel oxides/hydroxides, enhancing OER catalytic performance.